Etnografi Masyarakat dan Hukum Adat Kabupaten Humbang Hasundutan Sumatera Utara - Yudhi Ramadani Harahap; Ibnu Hajar; Robert Sibarani (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
This scrip is a "blue print" of the community and customary law in Humbang Hasundutan District of North Sumatra. Aim to find solutions to resolve conflicts related to agrarian resources. Access rights to communal land, applied implementation in policy determination, exploration, conflict mitigation. Describe the legal system and local wisdom that live in indigenous peoples. The research research method uses qualitative research with the ethnographic approach of James P. Spradley. The technique of collecting data is in-depth interviews, participant observation and oral traditions. This ethnography is holistic-integrative, thick description, and qualitative analysis to get native's point of view. The results of the study revealed the mechanism of genological inheritance to children and closest relatives. Inheritance recognized as customary recession, panjaean land for boys or ulos na so buruk for boru girls. Mechanism of buying and selling ulos tu piso, dondon mortgage, giving, contract. Forms of social entities, bius, partolian, golat, huta, marga raja which are customary structures that play the role of holders of communal access rights. Decision-makers and dispute resolution, Pago-pago, Horja, Bius, Raja Nihuta, Bius Raja, Paradaton, Paripe, Nomads enculturation. The socio-political aspects of the community of Sionom Hudon, PBM, Sihas, Chair of the institution, Raja Nihuta, Bius Raja, Paradaton, Paripe.